Analysis of Implementation Factors of Safety and Health Program on Work Accident in CV. Pasific Harvest Muncar District Banyuwangi - Tri Suryo Wibowo (Journal for Quality in Public Health, 2019)
Human Resources (HR) occupies a strategic and important place among other resources. In this case the company needs to pay attention to the security of employees while working in the company. One form of protection is to provide Occupational Safety and Health (K3) employees. The purpose of this study was to analyze the most dominant factors affecting work accidents in CV. Pacific Harvest Muncar Banyuwangi. The research design used was cross sectional. The research population is All employees in the production department CV. Pacific Harvest of 273 people and a large sample of 162 people. The sampling technique using Simple random sampling anddata collection using questionnaires and then analyzed using multiple linear regression.The results showed that between attitudes to work accidents no significant effect with significant value = 0.001 <0.05).Between knowledge of accidents of work there is significant influence with significant value = 0,000 <0.05 and there is a behavioral effect on work accidents with significant value = 0.025 <0.05.Based on the research, it is necessary to make the knowledge about K3 more enhanced to form a safe attitude and behavior in working and obeying all regulations and SOP K3 applied by the company.